3y2-4y=1

Simple and best practice solution for 3y2-4y=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y2-4y=1 equation:



3y^2-4y=1
We move all terms to the left:
3y^2-4y-(1)=0
a = 3; b = -4; c = -1;
Δ = b2-4ac
Δ = -42-4·3·(-1)
Δ = 28
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{28}=\sqrt{4*7}=\sqrt{4}*\sqrt{7}=2\sqrt{7}$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-2\sqrt{7}}{2*3}=\frac{4-2\sqrt{7}}{6} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+2\sqrt{7}}{2*3}=\frac{4+2\sqrt{7}}{6} $

See similar equations:

| 0.4h-5.3=47 | | x^2-438342346237482342+9565642343*5324454523344=0 | | 3-x+50=5 | | -106+16y=6(4y-4)-8 | | 3000=120x+500 | | -21.6=-0.0035a+40 | | -8m+7=m+7+7m | | -13=7x+1-4x | | x^2+12=85 | | 3(x2+1)=(x+2)2 | | (3x-1)+13=6 | | 15+3x=26x+2 | | 3u−4=8 | | 11x-3x+6=6 | | -13=7x-1-4x | | 2x-4=8x-43 | | 4/2x=8/x+2 | | 3=-(4x+7)+3x | | 18=|6x+12|=-24 | | 8g+15=64 | | 5.2=a-0.45.2=a-0.4 | | 34+4n=28 | | 11(x-2)+7=5+x-20 | | 1-3(2x)=7 | | 9(-7w+5)=-48-63w | | (2x+8)+8x=12 | | 3x2+5x-2=2x-5 | | 25x+14x=175 | | (2x+3)^2=)3x-4)^2 | | 3.3−|3+x|=−2.4 | | (X)=5x-2 | | 4a/2=5 |

Equations solver categories